STRATEGI PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA DI DESA KAMASAN KABUPATEN KLUNGKUNG - Iswari Ardi, Ida Ayu Gde Widya; Yudharta, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
This study aims to analyze the strategies that have been carried out and the ideal ones needed by the village government in developing Kamasan Tourism Village. The study has using qualitative descriptive. The technique of determining the informants used is purposive technique. Sources of data used are primary and secondary data. The data collection techniques are by means of interviews, observation and document study. The data analysis technique used is a SWOT analysis. Based on the study using SWOT matrix analysis, four alternatives were obtained from SO, WO, ST, WT which became the alternative strategy choices as a priority for future strategies such as; expanding cooperation, communication and community involvement through the application of CBT, optimizing tourism marketing activities, optimizing tourism potential and developing novelty tours, improving the quality of human resources. Keywords: Strategic Planning Process, Tourism Village Development, Kamasan Village